Answer:
x=7
Step-by-step explanation:
−9(x + 6) + 60 = 13 − 10x
Distribute
−9x -54 + 60 = 13 − 10x
Combine like terms
-9x +6 = 13 -10x
Add 10x to each side
-9x+10x +6 = 13-10x+10x
x +6 = 13
Subtract 6 from each side
x+6-6=13-6
x = 7
The discount price will be 0.8X dollars.
Step-by-step explanation:
Given,
Price of an item = X dollars
Discount = 20%
Amount of discount = 20% of Price of item
Amount of discount =
Price of item after discount = Price of item - Amount of discount
Price of item after discount = X-0.2X = 0.8X dollars
The discount price will be 0.8X dollars.
Keywords: discount, subtraction
Answer:
(15, 12)
Step-by-step explanation:
Let's generate two systems of equations that fit this scenario.
Number of trips to the airport = x
Number of trips from the airport = y
Total number of trips to and from the airport = 27
Thus:
=> equation 1.
Total price for trips to the Airport = 14*x = 14x
Total price of trips from the airport = 7*y = 7y
Total collected for the day = $294
Thus:
=> equation 2.
Multiply equation 1 by 7, and multiply equation 2 by 1 to make both equations equivalent.
7 × ![x + y = 27](https://tex.z-dn.net/?f=%20x%20%2B%20y%20%3D%2027%20)
1 × ![14x + 7y = 294](https://tex.z-dn.net/?f=%2014x%20%2B%207y%20%3D%20294%20)
Thus:
=> equation 3
=> equation 4
Subtract equation 4 from equation 3
-7x = -105
Divide both sides by -7
x = 15
Substitute x = 15 in equation 1
![x + y = 27](https://tex.z-dn.net/?f=%20x%20%2B%20y%20%3D%2027%20)
![15 + y = 27](https://tex.z-dn.net/?f=%2015%20%2B%20y%20%3D%2027%20)
Subtract both sides by 15
![y = 27 - 15](https://tex.z-dn.net/?f=%20y%20%3D%2027%20-%2015%20)
![y = 12](https://tex.z-dn.net/?f=%20y%20%3D%2012%20)
The ordered pair would be (15, 12)
Answer:
I assume your goal is to rationalize the denominator -
So you need to multiply the denominator by its conjugate.
So we have:
![\frac{\sqrt{x} }{\sqrt{x}-\sqrt{7} } *\frac{\sqrt{x} +\sqrt{7} }{\sqrt{x} +\sqrt{7}}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7Bx%7D%20%7D%7B%5Csqrt%7Bx%7D-%5Csqrt%7B7%7D%20%7D%20%2A%5Cfrac%7B%5Csqrt%7Bx%7D%20%2B%5Csqrt%7B7%7D%20%7D%7B%5Csqrt%7Bx%7D%20%2B%5Csqrt%7B7%7D%7D)
->
![\frac{x-\sqrt{7}\sqrt{x} }{x-7}](https://tex.z-dn.net/?f=%5Cfrac%7Bx-%5Csqrt%7B7%7D%5Csqrt%7Bx%7D%20%7D%7Bx-7%7D)
gg
Answer:
False
Step-by-step explanation: